(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background Viruses are recognized as significant contributors to cancer development, accounting for approximately 15–20% of human malignancies worldwide. Aim This review aims to provide a comprehensive overview of the major cancer-causing viruses and to elucidate their oncogenic mechanisms and clinical implications. Key point The review focuses on Human Papillomavirus (HPV), Hepatitis B and C viruses (HBV,and HCV), Epstein–Barr virus (EBV), Human T-cell Leukemia Virus type 1 (HTLV-1), and Kaposi’s Sarcoma-associated Herpesvirus (KSHV). Each virus employs distinct molecular strategies to manipulate host cellular pathways, promoting uncontrolled cell proliferation, evasion of apoptosis, and genomic instability hallmarks of cancer. The review explores viral integration, expression of viral oncogenes, immune evasion, and chronic inflammation as key mechanisms in virus-induced carcinogenesis. Additionally, the clinical implications of these findings are discussed, including the development of diagnostic biomarkers, and targeted antiviral therapies. Conclusions Understanding the interplay between viral infection and tumor biology offers valuable insights into cancer prevention, early detection, and novel therapeutic approaches.